2001
DOI: 10.1111/1530-2415.00006
|View full text |Cite
|
Sign up to set email alerts
|

The Prevention of Homelessness Revisited

Abstract: Conceptual and methodological problems plague efforts to prevent homelessness. Attempts to identify individuals at risk are inefficient, targeting many people who will not become homeless for each person who will. Such interventions may do useful things for needy people, but evidence that they prevent homelessness is scant. Subsidized housing, with or without supportive services, has ended homelessness for families and played a key role in ending it for people with serious mental illnesses. Other risk factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
100
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(101 citation statements)
references
References 56 publications
1
100
0
Order By: Relevance
“…While studies have identified many characteristics that increase the general risks of housing problems, they have been less successful in predicting specific transitions to or from housing insecurity (Shinn et al, 2001). Recognising the unpredictability of homelessness episodes, O'Flaherty (2004;2010) hypothesised that homelessness results mainly from badluck shocks striking vulnerable people.…”
Section: Previous Studiesmentioning
confidence: 99%
“…While studies have identified many characteristics that increase the general risks of housing problems, they have been less successful in predicting specific transitions to or from housing insecurity (Shinn et al, 2001). Recognising the unpredictability of homelessness episodes, O'Flaherty (2004;2010) hypothesised that homelessness results mainly from badluck shocks striking vulnerable people.…”
Section: Previous Studiesmentioning
confidence: 99%
“…To provide universal access to Housing First may be untenably expensive, however by not doing so the problems that it is intended to address continue to be allowed to fester among all but the most severely in need. Prevention of these problems at entry point may be a greater use of resources for the future (Shinn & Baumohl, 1999). Further research and economic analysis is needed to provide ground on which to widen the debate.…”
Section: -Providing a Service To Previously Excluded Groupsmentioning
confidence: 99%
“…Returning to US work this point was succinctly recognised by Shinn & Baumohl (1999) noting that practitioners should 'remember that preventing homelessness is not identical to ending poverty, curing mental illness, promoting economic self-sufficiency, or making needy people healthy, wealthy and wise'. Rather the goals that are being pursued have to be kept 'clearly in mind' (Shinn & Baumohl, 1999: 13-1).…”
Section: Continuums Of Care)mentioning
confidence: 99%
“…Meer publicaties zijn te vinden over de preventie van dakloosheid (Shinn, Baumohl & Hopper, 2001;Crane, Fu & Warnes, 2004;Crane et al, 2006;Backer & Howard, 2007;Burt, Pearson & Montgomer, 2007;Culhane, Metraux & Byrne, 2011). Maar zoals Culhane et al (2011, p. 296) aangeven: " […] there is much about homelessness prevention that still needs to be understood."…”
mentioning
confidence: 99%